Evidências de validação de um protocolo para assistência às pessoas com úlceras venosas em serviços de alta complexidade - Dantas, Daniele Vieira (2014)
Venous ulcers are lesions resulting from chronic venous insufficiency, venous valvular abnormalities and venous thrombosis. Its occurrence has been growing with the increase in life expectancy of the world population. Considered as fundamental aspects in the approach to the person with venous ulcer care with the interdisciplinary approach, adoption of protocol-specific knowledge, technical skill, coordination between levels of care complexity of the Health System and active participation of patients and their families, a holistic perspective. The construction of a clinical protocol for people with venous ulcers can help professionals of high complexity services in patient assessment and the establishment of quality care in a systematic way and focused on the factors that interfere with wound healing. Thus, this study aimed to analyze the evidence of validation of a clinical protocol for people with venous ulcers treated at high-complexity services. This is a methodological study with a quantitative approach, developed in three stages: literature review, evidence of content validity and evidence of validation in the clinical context. Approved by the Federal University of Rio Grande do Norte Research Ethics Committee (Opinion: 147.452 and CAAE: 07556312.0.0000.5537). The literature review was conducted in August and September 2012, becoming the basis for the construction of the protocol. Then the evidence of content validity, which included 53 judges (experts) selected by the Lattes platform to evaluate the protocol items was performed. The judges were contacted by e-mail and rated the protocol via Google Docs <docs.google.com>. After analyzing the ratios obtained in this step, which reported kappa between 0.75 and 0.96 and between 0.80 and 0.98 IVC, and the suggestions of the judges, the protocol was adjusted and subjected to empirical evidence to validate the clinical setting at the University Hospital Onofre Lopes in Natal / RN. Evidence of validation in the clinical setting involved 4 judges who acted in pairs (paired) evaluated 32 patients with venous ulcers in the clinical context of high complexity. In both stages, we used the Kappa Index and Content Validity Index to analyze the responses of the judges. The parameters set as acceptable for these indices were: Kappa ≥ 0.61 and Content Validity Index > 0.80. Any evidence of content validity, as evidence of validation in the clinical context, the protocol items that have not reached Kappa and Content Validity Index established indices were excluded and some items were modified or added after suggestions. The process of content validation evidence and evidence of validation in the clinical setting allowed the improvement of the protocol for the care of people with venous ulcers initially proposed. The initial version of the protocol, built from the literature, contained 15 categories and 108 items; after evidence of content validity, remained the reduction to 15 categories with 91 items; the final version, clinically validated, is composed of the same 15 categories, 76 items. The protocol was validated in its content and in the clinical aspect, so we accepted the alternative hypothesis in the study. This protocol may contribute to the care system, allowing tailor behaviors and promote greater resolution in the treatment of people with venous ulcers in health services of high complexity